Psychological Factors Associated With Anterior Cruciate Ligament Reconstruction Recovery - Christino, Melissa A. (Orthop J Sports Med, 2016)
BACKGROUND: Psychological factors may have underappreciated effects on surgical outcomes after anterior cruciate ligament (ACL) reconstruction; however, few studies have investigated the relationship between specific psychological factors, objective clinical data, and patient-oriented outcomes. PURPOSE: Psychological factors are significantly associated with patient perceptions and functional outcomes after ACL reconstruction. The purpose of this study was to demonstrate relationships between self-esteem, health locus of control, and psychological distress with objective clinical outcomes, patient-oriented outcomes, and return to sport. STUDY DESIGN: Cross-sectional study; Level of evidence, 3. METHODS: Twenty-seven patients who were 6 to 24 months post–computer-assisted ACL reconstruction by a single surgeon consented to participate in the study (52% response rate). Participants had a 1-time visit with a physician consisting of: a physical examination, a single-leg hop test, KT-1000 arthrometer measurements, and survey completion. Psychological measures included the Multidimensional Health Locus of Control Scale, Rosenberg Self-Esteem Scale, and Brief Profile of Mood States. Outcome measures included the Tegner activity scale, International Knee Documentation Committee (IKDC) Subjective Knee Score, Knee injury and Osteoarthritis Outcome Score–Quality of Life subscale (KOOS-QOL), and Short Form–36 (SF-36). Patient charts were also reviewed for pertinent operative details. RESULTS: The mean age of patients (±SD) was 25.7 ± 8.4 years, and the mean duration of time since surgery was 16.5 ± 5.9 months. The majority (89%) of the patients identified themselves as athletes, and of these, 65% reported returning to sports at a competitive level. Sport returners were found to have higher levels of self-esteem (P = .002) and higher reported KOOS-QOL scores (P = .02). Self-esteem was significantly associated with IKDC scores (r = 0.46, P < .05), KOOS-QOL scores (r = 0.45, P < .05), and SF-36 subscales of general health (r = 0.45, P < .05) and physical functioning (r = 0.42, P < .05). Internal locus of control was significantly correlated with performance on single-leg hop test (r = 0.4, P < .05). Objective knee stability measurements did not correlate with subjective outcomes. CONCLUSION: Self-esteem levels and locus of control had significant relationships with functional test performance and validated outcome measures after ACL reconstruction. Sport returners had significantly higher self-esteem levels than those who did not return to sports, without observable differences in knee stability or time since surgery.